2011
DOI: 10.5144/0256-4947.2011.289
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sickle Cell Disease in Saudi Arabia

Abstract: Sickle cell disease (SCD) is an autosomal recessive disorder characterized by production of abnormal hemoglobin S and is associated with high morbidity and mortality. Information about the prevalence of SCD in Saudi Arabia is patchy and probably underestimated, but studies have reported that SCD is a relatively common genetic disorder in this part of the world. The prevalence of SCD in Saudi Arabia varies significantly in different parts of the country, with the highest prevalence is in the Eastern province, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The Sickle Cell Anemia affected about 100, 000 people of the United States, among them 2 million are carrier 3 however, embarked decline in the mortality 4 and the mean age of death in male is 53 years and in female about 58 years 5 . In Pakistan, 0.5-1% of populationis carriers of Hemoglobin S 6 , whereas about 5.1% of prevalence found in Karachi 7 . The prevalence of Sickle cell disease is 1.4% in some regions of Saudi Arabia 8 .…”
Section: Introductionmentioning
confidence: 98%
“…The Sickle Cell Anemia affected about 100, 000 people of the United States, among them 2 million are carrier 3 however, embarked decline in the mortality 4 and the mean age of death in male is 53 years and in female about 58 years 5 . In Pakistan, 0.5-1% of populationis carriers of Hemoglobin S 6 , whereas about 5.1% of prevalence found in Karachi 7 . The prevalence of Sickle cell disease is 1.4% in some regions of Saudi Arabia 8 .…”
Section: Introductionmentioning
confidence: 98%
“…The highest frequency of sickle cell disease was found in tropical regions, particularly sub-Saharan Africa, India and the Middle-East, [9] with prevalence of sickle-cell trait (HbS) of 4.2% in Saudi Arabia and 0.26% of sickle cell disease (HbSS) with the highest prevalence in the Eastern province. [10] A population-based study from Bahrain has confirmed a high prevalence of VDD, especially in females, that shows a seasonal variation. [11] In this study we assess the prevalence of VDD in patients with SCD (HbSS) in Bahrain and evaluate the clinical predictors of VDD in such patients.…”
Section: Introductionmentioning
confidence: 98%
“…The highest prevalence of SCD in Saudi Arabia is in the Eastern province. [28] Sickle cell diagnosis raises concerns about the affected child's life span. With appropriate clinical management supported by nurses' involvement in learning and education about their children' disease, 95 % of children will live beyond the age of 18.…”
Section: Significance Of the Studymentioning
confidence: 99%